Compiler Design Life Cycle And Comparison of Programming Languages - AL-Bakhrani, Ali A.; Hagar, Abdulnaser A.; Hamoud, Ahmed A.; Gawali, Bharti W.; Manza, Ramesh (International Journal of Psychosocial Rehabilitation, 2020)
Python is a popular object-oriented language for programming for Python. Sometimes programmers spend a lot of time on running the program, while at the same time on code size. It creates the code more complex and untrustworthy, that reduces code efficiency So many compilers are currently available, like C, Java, C++, C #, python and so on. The code optimizing techniques for a python compiler have been researched separately and we come across new strategies for code optimization which is a clever way to do python code. In this paper we have done a compiler application and it has been written in five programming languages which we mentioned above where we have made a comparison between those languages in order to reach the best suitable language for building the compiler that help the programmer and facilitate the construction process and also the time to execution code is less and also less memory and less code size.